APOBEC3 family proteins as drivers of virus evolution - Jonathan, Michael; Ikeda, Terumasa (Frontiers in Virology, 2023)
The apolipoprotein B mRNA editing enzyme catalytic polypeptide-like (APOBEC) family consists of cytosine deaminases implicated in diverse and important biological functions. APOBEC3 (A3) proteins belong to the APOBEC/AID family, and they catalyze the deamination of cytosine to uracil in single-stranded DNA and, to a lesser extent, in RNA substrates. In humans, seven A3 genes have been identified (A3A, A3B, A3C, A3D, A3F, A3G, and A3H). The introduction of lethal G-to-A or C-to-U mutations into certain viral genomes leads to virus inactivation. However, the mutagenic capability of A3 proteins could serve as a source of mutations to drive virus evolution. Therefore, recent studies have implied the role of A3 proteins in aiding the evolution of viruses, conferring them with severe manifestations such as drug resistance and/or immune evasion. In this review, we discuss in depth the interactions of A3 proteins with viruses that infect humans and our self-proteins.